Rational Emotive Behaviour Therapy Counselling with Imagery Technique to Improve Resilience of Teenage as Victims of Divorce - Andini, Rena; Hafina, Anne; Farida, Euis (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
A harmonious family is hoped by every teenagers however happiness can change when the conflict arises caused by the family member such as parental divorce which can lead to problems for teenagers as the victim of divorce. Children who are entering adolescence have understood the occurrence of divorce between their parents and normally will feel hurtful and anger which can cause the negative character such as depression, committing juvenile delinquency, and others. Resilience ability is very necessary for teenager divorce-victim, who is fragile to behavioral problems, to prevent teenagers from falling into negative things. Through REBT counseling technique, by imagery technique, teenagers can be built to straighten out the negative beliefs in order to positively face problems as a result of their parental divorce.